Jesus the sage the pilgrimage of wisdom - Witherington, Ben, III, 1951- (Edinburgh, Scotland T and T Clark, 1994)
Includes bibliographical references and index.
Keywords: Bible. O.T. wisdom literature -- relation to New Testament; Jesus Christ -- Old Testament teaching